2009
DOI: 10.1007/s00705-008-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of potato virus X coat protein capacity for assembly with RNA after His-tag removal

Abstract: We found that the fusion of hexahistidine (H)6 tag to the potato virus X (PVX) coat protein (CP) abolished its ability to be assembled with viral RNA into helical nucleoprotein virus-like particles (VLPs). Instead, irregular agglomerates were produced upon incubation of PVX RNA with (H)6-tagged PVX CP. A factor Xa recognition site, IEGR, was inserted upstream of the CP coding sequence. Removal of the (H)6 tag from PVX CP by Xa protease restored its ability to bind RNA and to assemble VLPs. In addition to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…For the mixtures where AltMV RNA was incubated with each of the proteins individually, the gel retardation assay revealed that the material was held up at the start of the gel. Data from our previous experiments suggest that the presence of histidine residues can lead to nonspecific aggregation of recombinant proteins with RNA [20]. This may explain the observation that RNA incubated with recombinant protein ER6 was retained in the gel at the start level.…”
Section: 3mentioning
confidence: 91%
“…For the mixtures where AltMV RNA was incubated with each of the proteins individually, the gel retardation assay revealed that the material was held up at the start of the gel. Data from our previous experiments suggest that the presence of histidine residues can lead to nonspecific aggregation of recombinant proteins with RNA [20]. This may explain the observation that RNA incubated with recombinant protein ER6 was retained in the gel at the start level.…”
Section: 3mentioning
confidence: 91%
“…Instead, PVX RNA interaction with PVX TGBp1 turns the protein helix into a metastable state and further interaction with a ribosome triggers release of the free RNA, which results in RNA translation and formation of virus-specific products [15,20,31]. A defining role in this process is played by the conformational states of PVX CP and TGBp1 [32,33], so that translation of an RNA within a vRNP indicates that PVX CP of the vRNP has the native protein structure [15].…”
Section: Pvx Cp Incubation With the 3 0 -Terminal Functional Fragmentmentioning
confidence: 96%
“…De hecho, únicamente se ha descrito la interacción TGB1-CP para este grupo (Samuels et al, 2007). Hasta el momento existían dos modelos para explicar el transporte de Potexvirus a través de los PDs: uno en el que se postulaba que el PVX atravesaría el PD en forma de virión modificado (Santacruz et al, 1998) con la ayuda deTGB2 ,mediante su interacción con el genoma viral (Hsu et al, 2009) y otro en el que la partícula vírica consistiría en un complejo RNP formado por la TGB1, la CP y el vRNA (Lough et al, 2000), lo cual se asemejaría más a lo que ocurre con BMV o AMV (Karpova et al, 2006;Lukashina et al, 2009;Zayakina et al, 2009). Sin embargo, recientemente estudios basados en la utilización de virus quimera han esclarecido el papel que desempeña la CP en este proceso y han demostrado que la formación del virión es prescindible para el movimiento célula a célula pero necesaria para el movimiento sistémico (Betti et al, 2012).…”
Section: Movimiento Viral Guiado Por Túbulosunclassified